AB0126 EXPRESSION CHARACTERISTICS OF ADENOSINE DEAMINASES ACTING ON RNA-1 IN SYSTEMIC LUPUS ERYTHEMATOSUS AND ITS CORRELATION WITH SERUM IFN-Α. (2nd June 2020) - Di, X.; Gao, F.; Gao, C.; Zhang, C.; Sun, W.; Liang, W.; Yao, M.; Wang, Q.; Zheng, Z.
Abstract : Background: SLE is a multisystem autoimmune disease characterized by the production of multiple autoantibodies and loss of immunity against autoantigens in various tissues. SLE patients have significantly elevated RNA editing levels and the potential to produce new autoantigens. 1 ADAR1 is an RNA A-I editing enzyme that converts adenine to hypoxanthine and contributes to SLE pathogenesis. 2 Objectives: Dama demonstrated the upregulation of ADAR1p150 expression in SLE T cells, B cells, PBMCs, and NK cells; 3 however, the following issues were not reported in detail: 1. specific alterations in ADAR1 expression in PBMCs collected from SLE patients with varying degrees of the disease and its correlation with serum IFN-α levels; 2. association between ADAR1 and clinical indicators; and 3. ADAR1 expression in renal tissue of LN patients. Our study therefore aimed to elucidate the abovementioned points. Methods: We used qRT-PCR to determine ADAR1 expression levels in PBMCs and renal tissues of controls and SLE patients. We also conducted immunohistochemical studies to detect positive ADAR1 expression rate in renal cells of controls and LN patients. Results: ADAR1 expression was higher in PBMCs of SLE patients than in those of controls and was positively correlated with SLEDAI. When serum IFN-α levels in SLE patients decreased <260.0 pg/mL, ADAR1 expression in PBMCs increased with the increase in IFN-α concentration, and serum IFN-α may regulate ADAR1 level in PBMC in SLE patients, which may require the participation of serum IgG antibody and related immune complex. However, there was no significant difference between the expression in renal tissues in all patients. Conclusion: There was a certain correlation between ADAR1 expression and serum IFN-α levels in PBMCs of SLE patients. References: [1]Roth SH, Danan-Gotthold M, Ben-Izhak M, et al. Increased RNA Editing May Provide a Source for Autoantigens in Systemic Lupus Erythematosus. Cell Rep 2018; 23: 50-57. [2]Hogg M, Paro S, Keegan LP and O'Connell MA. RNA editing by mammalian ADARs. Adv Genet 2011; 73: 87-120. [3]Laxminarayana D, Khan IU, O'Rourke KS and Giri B. Induction of 150-kDa adenosine deaminase that acts on RNA (ADAR)-1 gene expression in normal T lymphocytes by anti-CD3-epsilon and anti-CD28. Immunology 2007; 122: 623-633. Disclosure of Interests: None declared